The effects of hydrogen peroxide and lipopolysaccharide on rat alveolar L2 cells. (14th September 2017) - Kang, Eun Kyeong; Kim, Han Suk
ABSTRACT: Purpose : This study aimed to investigate differential cell responses of alveolar epithelial cells (AECs) after treatments with lipopolysaccharide (LPS) and hydrogen peroxide (H2 O2 ) to mimic the exposure to inflammation and oxidative stress and the mechanisms of a double-hit model of apoptosis.Materials and Methods : AECs were cultured and treated with combinations of 1 μg/mL of LPS and 500 μM H2 O2 as follows: LPS-only at 0 h, LPS at 0 h with H2 O2 at 6 h (LPS + H2 O2 ), H2 O2 -only at 0 h, H2 O2 at 0 h with LPS at 6 h (H2 O2 + LPS), and control. We investigated mRNA expression (TNF-α, Fas, Fas ligand, Bax, Bcl-2, Caspase-7), protein expression (Fas, Bax, Bcl-2, Caspase-7) and apoptosis (Caspase-3 activity, TUNEL assay) at 0, 3, 6, 9, 12, and 24 h.Results : In the H2 O2 + LPS group, the Caspase-7, and Fas mRNA levels were significantly higher than the other groups at 9 h and 12 h, and Bax was higher at 12 h. The Bax/Bcl-2 protein expression ratio was significantly higher in the H2 O2 + LPS group than that of the other groups at 12h and 24h. Apoptotic index was highest in the H2 O2 + LPS group at 24 h.Conclusions : The sequence of stimulation may modify the cell response in rat AECs. The results suggest that previous oxidative stress and subsequent LPS-induced inflammation primarily influence apoptosis of L2 cells by up-regulation of cell signaling.